Effect of a supplementary periodized complex strength training and tapering period on postactivation potentiation of sport-specific explosive performance in adolescent national-level fencers - Kontochristopoulos, N.; Bogdanis, G. C.; Paradisis, G.; Tsolakis, C. (The Journal of Strength and Conditioning Research, 2021)
This study examined the effects of strength training and tapering on countermovement jump (CMJ), change of direction (COD), and step-lunge (SL) after a conditioning activity in adolescent fencers. Twenty fencers (age: 15.8 ± 1.2 years) were randomly assigned to experimental (EXP, n = 10) group and control (CON, n = 10) group. EXP and CON groups performed 8 weeks of fencing training (4 times per week), while EXP group performed a supplementary strength training program twice per week, including a hypertrophy (first 2 weeks) and a complex strength training period (6 weeks). A 14-day tapering period with reduced training volume was then applied in both groups. Conditioning activity consisted of 3 × 3 seconds of maximal voluntary isometric contraction (MVIC; half-squat; knee angle = 90°), followed by either CMJ or COD or SL performance measurements in 3 different testing sessions 24 hours apart. There was no performance enhancement in all tests for both EXP and CON groups, after the conditioning MVIC before training (p > 0.05). After training, half-squat dynamic strength (1 repetition maximum [1RM]) was significantly increased only in the EXP group (from 74.8 ± 20.0 to 127.0 ± 28.9 kg, p = 0.001) and maintained after tapering. After tapering, baseline CMJ height was significantly increased only in the EXP group (from 27.2 ± 4.6 to 30.9 ± 3.8 cm, p = 0.003). Contrary to our hypothesis, the increase in 1RM and CMJ was not followed by a postactivation potentiation enhancement in all tests (p > 0.05), possibly because of the relatively low strength and jumping performance of fencers. Thus, adolescent high-level fencers do not exhibit a performance increase after MVIC, and this was not modified by the supplementary strength training protocol used.